Normal faciolingual inclination of tooth crowns for Iraqi adolescent in Mosul City - Nada M Al-Sayagh (University of Mosul, College of Dentistry, 2004)
The purposes of this study are to determine the faciolingual inclinations of tooth crowns in Class I normal occlusion of Iraqi adolescent in Mosul City, investigate the possible significant differences between genders, and determine the cor-relation of the faciolingual inclination of teeth crown with each others.The sample of this study consisted from 35 Iraqi adolescents (19 males and 16 females) aged 12-16 years selected according to certain criteria from Mosul City. Stone casts were taken for each subject, the faciolingual inclinations were made on the dental models of the subjects by using torque angle gauge.The data were analyzed with the Statistical Package for Social Sciences prog-ram and it was found that each tooth dist-ally to the central incisor had more lingual inclination than did its neighbor. The females had more labial inclination of upper lateral incisor and more lingual inclination of the lower canine, premolars and first molar as compared with the males. Most intraarch teeth torque correlation were positive and decreased with remoteness while most interarch teeth correlation showed weak negative correlation.